A study of daily variations of the outdoor background radiation measured in continuous mode in Federation of Bosnia and Herzegovina. (June 2020) - Avdic, Senada; Demirovic, Damir; Kunosic, Suad; Pehlivanovic, Beco; Kadic, Irma; Ilic, Zorana
Abstract: Systematic monitoring of environmental radionuclides with the aim of early warning in emergency situations in Federation of Bosnia and Herzegovina (FB&H) was established in 2004. Environmental radiation monitoring network includes six automatic monitoring stations over the FB&H territory. This paper deals with the first study of ambient dose equivalent rates collected over the period of 2012–2017 with the main objective to investigate the temporal and spatial variations in the outdoor background radiation. The correlation analysis between the continuously acquired gamma dose rates and the simultaneous meteorological records on a daily basis contributed to a better interpretation of daily variations of the measured data. Derivation of the net ambient dose equivalent rates and the terrestrial radiation component from routine monitoring data was carried out as a prerequisite for adequate monitoring of background radiation. In addition, the terrestrial background component was estimated from the soil radionuclides at the same monitoring sites. The correlation analysis in a form of bivariation statistics between activity concentration of each pair of primordial radionuclides in the soil samples show that primordial radionuclides are not uniformly distributed over the FB&H territory. The mean values with the combined standard uncertainties for the terrestrial component evaluated from the soil radionuclides of (74.4 ± 12.5) nSv/h and from routine monitoring data of (81.8 ± 17.9) nSv/h are within the ranges reported for East and South European countries. The sources of statistical and systematic uncertainties were analyzed. The applied procedure of the terrestrial radiation component evaluation based on the daily monitoring data could be of complementary significance related to the existing evaluation procedures with a smaller sampling time of monitoring records. The results of the present study indicate that the acquired monitoring data are reliable enough to correctly assess the radiological situation in FB&H. In case of an emergency situation, the results obtained could be useful for a better identification of contaminated area. Highlights: Preparation of ambient dose rate time series for analysis. Temporal and spatial variations of the outdoor background radiation on a daily basis. Correlation analysis between dose rates and simultaneous meteorological records. Net dose rates and terrestrial radiation evaluation based on daily monitoring data. The results could be useful for a better identification of contaminated area.